Trends, Features and Problems of the Development of Nuclear Energy in France - A. B. Sekacheva (Мир новой экономики, 2022)
This article analyses the trends and problems associated with the peculiarities of the development of nuclear energy in France. This country has always paid particular attention to the fuel and energy sector. Its significant potential allows it to occupy one of the top places in the world in the use of nuclear technologies in the national economy. At the same time, the relatively hostile policy of the European Union concerning nuclear energy in connection with the implementation of its course on the “green” economy creates many problems in the relations of Paris with the leadership of this integration association. Given that Germany in 2022 completely closes its nuclear power plants (NPP), and France becomes the leading country in the EU for the use of nuclear energy, the leadership of this country under the influence of political factors often has to make mutually exclusive decisions in this area. France’s position as the most significant nuclear power in the EU is complicated because it faces increasing competition in the global nuclear market. The leading positions on it are traditionally occupied by the United States, Russia, and China. Time will tell whether France will be able to cope with these threats. One thing is certain: France seeks to maintain and strengthen its position as the leading nuclear power in the EU and worldwide. France’s long-term experience in designing and building nuclear power plants and ensuring their safe operation can also be useful for Russia, as it is generally recognized that our country has been and is one of the world leaders in nuclear energy.